2020
DOI: 10.1002/joc.6685
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the relationship between Indian Ocean dipole and Indian summer monsoon rainfall in early and recent multidecadal epochs during different phases of monsoon

Abstract: In this study, we explored the changes in the Indian Ocean Dipole-Indian summer monsoon rainfall (IOD-ISMR) relationship from early (1951-1980) to recent (1986-2015) multidecades during onset (June), peak (July-August) and withdrawal (September) phases of Indian summer monsoon. The analyses indicate

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 53 publications
2
3
0
Order By: Relevance
“…This is not surprising in regions like Southern Asia (Figures 5a and 5b) with salient contrast between dry and wet seasons and about 80% annual rainfall falls in the monsoon season, that is, June to September (Bhatla et al., 2016). Specifically, the warm‐dry to wet swings concentrate between mid‐June and late‐June (Figure 5a), consistent with the period from central Indian seeing the abrupt monsoon onset (B. Wang & LinHo, 2002) to rainfall starting to cover the entire Indian region (Hrudya et al., 2021). The occurrence of the opposite swings peak in September and October when Indian monsoon gradually withdraws and begins to transform to winter monsoon (Figure 5b).…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…This is not surprising in regions like Southern Asia (Figures 5a and 5b) with salient contrast between dry and wet seasons and about 80% annual rainfall falls in the monsoon season, that is, June to September (Bhatla et al., 2016). Specifically, the warm‐dry to wet swings concentrate between mid‐June and late‐June (Figure 5a), consistent with the period from central Indian seeing the abrupt monsoon onset (B. Wang & LinHo, 2002) to rainfall starting to cover the entire Indian region (Hrudya et al., 2021). The occurrence of the opposite swings peak in September and October when Indian monsoon gradually withdraws and begins to transform to winter monsoon (Figure 5b).…”
Section: Resultssupporting
confidence: 73%
“…Specifically, the warm-dry to wet swings concentrate between mid-June and late-June (Figure 5a), consistent with the period from central Indian seeing the abrupt monsoon onset (B. Wang & LinHo, 2002) to rainfall starting to cover the entire Indian region (Hrudya et al, 2021). The occurrence of the opposite swings peak in September and October when Indian monsoon gradually withdraws and begins to transform to winter monsoon (Figure 5b).…”
Section: Significant Shift In Swing's Seasonalitysupporting
confidence: 73%
“…A recent study by Hrudya et al . (2021) revealed a phase change from positive (1951–1980) to negative correlation (1986–2015) of Indian Ocean dipole (exists between Western and southeastern tropical Indian Ocean) with the monsoon rainfall. The phase changes could have weakened the overall correlation in the current study considering a period from 1948 to 2020.…”
Section: Resultsmentioning
confidence: 99%
“…Further mapping the correlation of these teleconnections (ENSO based on SSTs averaged over the Nino 3.4 region and IOD based on DMI) with the gridded drought indices in India show significant values for ENSO (Figure S7) and weak correlation for the IOD (Figure S8). A recent study by Hrudya et al (2021) revealed a phase change from positive to negative correlation of Indian Ocean dipole (exists between Western and southeastern tropical Indian Ocean) with the monsoon rainfall. The phase changes could have weakened the overall correlation in the current study considering a period from 1948 to 2020.…”
Section: Enso Teleconnection With Concurrent Droughtsmentioning
confidence: 99%
“…It starts developing in May and attains its peaks in fall (September-October-November; SON) and decay in winter (December-January-February; DJF) with strong year-to-year variability. IOD profoundly impacts the strength of seasonal Indian summer monsoon rainfall (ISMR) and its variability (Ashok and Saji, 2007;Hrudya et al, 2021). The number of IOD events is projected to increase in a warming climate, particularly the number of intense positive IOD events (Cai et al, 2021(Cai et al, , 2014.…”
Section: Introductionmentioning
confidence: 99%